Awareness of dental diseases and oral health behaviour among dental and medical students of a Nigerian university (2016)
Aim of the study. To assess the effects of change in curriculum on the oral health knowledge and behaviour among the third and fourth year medical and dental students, and their use of dental services. Methods. A self-administered questionnaire was used to assess, among other things, the knowledge of respondents of dental diseases and possible risk factors. Results. Two hundred and thirty-seven respondents filled and returned the questionnaires, out of which 125 (52.7%) were females (with male:female ratio of 1:1.1). About 50% of the respondents were in 300 levels, consisting of 99 (82.5%) medical students. A higher percentage of 300 level medical students have better knowledge of diseases such as pulpitis, oral cancer and scurvy as possibly occurring within the mouth than their 400 level counterparts. Conclusions. There is a need not only to integrate dentistry into the curriculum of medical students, but also to re-assess constantly the impact of such on the quality of output from various medical schools.